From breaking the rule to making the rules: the adoption, entrenchment, and diffusion of gender quotas in France. (2nd April 2016) - Lépinard, Éléonore
Abstract : Once a country allergic to any type of preferential treatment or quota measure for women, France has become a country that applies gender quotas to regulate women's presence and representation in politics, the business sector, public bodies, public administration, and even some civil society organizations. While research has concentrated on the adoption of electoral gender quotas in many countries and their international diffusion, few studies focus on explaining the successful diffusion of gender quotas from politics to other domains in the same country. This paper proposes to fill this gap by studying the particularly puzzling case of a country that at one point strongly opposed the adoption of gender quotas in politics, but, in less than a decade, transformed into one of the few countries applying gender quotas across several policy domains. This paper argues that the legal entrenchment of the parity principle, the institutionalization of parity in several successive women's policy agencies, and key players in these newly created agencies are mainly responsible for this unexpected development. The diffusion of gender quotas in France thus offers an illuminating example of under which conditions women's policy agencies can act autonomously to diffuse and impose a new tool for gender equality.